PERLAKUAN DAN PEMBERIAN FASILITAS KEPADA PENANAM MODAL MENURUT PRESPEKTIF UU NO. 25 TAHUN 2007 TENTANG PENANAMAN MODAL - BONATUA EDYNATA MANIHURUK; BUDIMAN GINTING; MAHMUL SIREGAR (TRANSPARENCY, 2013)
Indonesia has ratified the Agreement on TRIM's (Agreement on Trade Related Investment Measures) through the implementation of Act 7 of 1994 on Foreign Investment, which of course affects how the government's treatment for both foreign and domestic investors, how the facility by the government to investors, and how government oversight of the investment activity. The method used in writing this paper is to study the data collected by the library (library research), which conducted a study using data from a variety of reading materials such as legislation, books, articles and internet are considered relevant to the issues discussed in the author this thesis. In investment activities, the Government of Indonesia implement the principle of equal treatment to foreign and domestic investors, even applies to all investors regardless of their country of origin investors. However, Article 6 paragraph (2), Act 25 of 2007 allows the government to provide the specific requirements of different investors who have certain privileges based on an agreement with Indonesia to a particular country, such as AFTA, ACFTA. Facilities / convenience provided by the government to investors were ten facilities, which should be adjusted according to the effectiveness and necessity of the investors in the business he started. Investment coordinating agency (BKPM) also plays running integrated one-stop service system (PTPS) as was stipulated in Presidential Regulation of BKPM No. 27 of 2009 concerning integrated one-stop service in the field of investment. Kata kunci: perlakuan, fasilitas, modal.